2015
DOI: 10.1371/journal.pone.0134581
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Genome Supports Sibling Species of Angiostrongylus costaricensis (Nematoda: Angiostrongylidae)

Abstract: Angiostrongylus costaricensis is a zoonotic parasitic nematode that causes abdominal or intestinal angiostrongyliasis in humans. It is endemic to the Americas. Although the mitochondrial genome of the Brazil taxon has been published, there is no available mitochondrial genome data on the Costa Rica taxon. We report here the complete mitochondrial genome of the Costa Rica taxon and its genetic differentiation from the Brazil taxon. The whole mitochondrial genome was obtained from next-generation sequencing of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…While the absence of a TΨC-arm is not uncommon in tRNAs encoded on nematode mt genomes (Watanabe et al 2014), differences were observed between isolates; 17 and 16 tRNAs lacked the TΨC-arm in the Chinese and Taiwanese mt genomes, respectively (Yong et al 2015 c ). A second 13 652 bp A. costaricensis mt genome was sequenced from a Costa Rican isolate (Yong et al 2015 d ) and compared to the original A. costaricensis mt genome, derived from a Brazilian parasite (Lv et al 2012). Based on phylogenetic analyses and genetic distances calculated for the mt genes, it was proposed that these parasites should be considered distinct members of a species complex, or sibling species (Yong et al 2015 d ).…”
Section: Molecular Biologymentioning
confidence: 99%
“…While the absence of a TΨC-arm is not uncommon in tRNAs encoded on nematode mt genomes (Watanabe et al 2014), differences were observed between isolates; 17 and 16 tRNAs lacked the TΨC-arm in the Chinese and Taiwanese mt genomes, respectively (Yong et al 2015 c ). A second 13 652 bp A. costaricensis mt genome was sequenced from a Costa Rican isolate (Yong et al 2015 d ) and compared to the original A. costaricensis mt genome, derived from a Brazilian parasite (Lv et al 2012). Based on phylogenetic analyses and genetic distances calculated for the mt genes, it was proposed that these parasites should be considered distinct members of a species complex, or sibling species (Yong et al 2015 d ).…”
Section: Molecular Biologymentioning
confidence: 99%
“…Both A. mackerrasae and A. cantonensis are genetically distinct from A. malaysiensis (p > 11%). A large genetic difference between sibling species is also found in the Costa Rican and Brazilian taxa of A. costaricensis (p = 16.17%, table 1; Yong et al , 2015b). The magnitude of the genetic difference is similar for the amino acid sequence of the 12 PCGs (table 1) as well as the complete mitochondrial cox1 nucleotide sequence (table 2).…”
Section: Resultsmentioning
confidence: 89%
“…Phylogenetic studies of Angiostrongylus and other nematode species often rely on the amplification of cox1 (Rodpai et al ., 2016; Eamsobhana et al ., 2018). The cox1 region is a useful ‘barcoding’ region that may enable distinguishing species or cryptic species, when inter and intra species distance is considered (Yong et al ., 2015 b ; Červená et al ., 2019). On the other hand, cox1 may not be the best marker for inferring species phylogeny (Dusitsittipon et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, cox1 may not be the best marker for inferring species phylogeny (Dusitsittipon et al ., 2018). Complete mtDNA sequences including the 12 protein coding genes are now frequently considered for phylogenetic reconstructions of nematodes demonstrating superior resolution support compared to single marker gene sequences (Gasser et al ., 2012; Lv et al ., 2012; Yong et al ., 2015 a , b , 2016; Červená et al ., 2019). Previous studies demonstrated a sister relationship between A. cantonensis and A. malaysiensis using either single gene phylogeny or whole mtDNA approaches (Rodpai et al ., 2016; Yong et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%